Cell–cell adhesions in embryonic stem cells regulate the stability and transcriptional activity of β‐catenin. Issue 13 (6th April 2022) - Bhattacharyya, Sinjini; Mote, Ridim D.; Freimer, Jacob W.; Tiwari, Mahak; Bansi Singh, Surya; Arumugam, Sandhya; Narayana, Yadavalli V.; Rajan, Raghav; Subramanyam, Deepa
Abstract : E‐cadherin (CDH1) is involved in maintaining cell–cell adhesions in embryonic stem cells (ESCs). However, its function in the context of cell fate decisions is largely unknown. Using mouse ESCs (mESCs), we demonstrate that E‐cadherin and β‐catenin interact at the membrane and continue to do so upon internalization within the cell. Cdh1 −/− mESCs failed to form tight colonies, with altered differentiation, marker expression and retention of pluripotency factors during differentiation. Interestingly, Cdh1 −/− mESCs showed dramatically reduced β‐catenin levels. Transcriptional profiling of Cdh1 −/− mESCs displayed a significant alteration in the expression of a subset of β‐catenin targets in a cell state‐ and GSK3β‐dependent manner. Our findings hint at hitherto unknown roles played by E‐cadherin in regulating the activity of β‐catenin in ESCs. Abstract : E‐cadherin loss causes mouse embryonic stem cells to display a scattered morphology along with a reduction in β‐catenin levels. Bhattacharyya et al. show that the expression of genes driven by β‐catenin cannot be restored by the stabilisation of the protein alone. Rather, the expression depends on the cell state and/or the presence of E‐cadherin along with the level of GSK3β activity.